THE ROMA IMAGES IN MIHÁLY MUNKÁCSY’S WORKS - Бойко , В’ячеслав (Art and Design, 2024)
Purpose of Article. The purpose of the article is to study of the stylistic and plot features of the Roma theme in the works of Mihály Munkácsy (1844–1944), an outstanding representative of the realist direction in the European fine arts of the second half of the XIXth century, who was born in Mukachevo of the Transcarpathia region. The methodology of the research is based on the historical-chronological, biographical, analytical and iconographic methods, which allow to analyse the specific features of the Roma images in the artist’s works. Results. The article highlights Mihály Munkácsy’s brief biography and the stages of his creative formation as the founder of the Hungarian national school of realistic painting in the XIXth century in the context of the historical era. The artist’s interest in landscape and biblical themes are shown. The exhibition activity in honor of the artist in the territory of Ukraine is briefly described, as well as the degree of development of the topic in the national scientific space. Mihály Munkácsy’s contribution to a wide range of Romani themea in fine realistic art has been proved. The analysis of such works as "Kazan" (1864), "Storm in the Pushta" (1867), and "Gypsy Camp" (1873) has allowed us stating that Mihály Munkácsy depicted the life of Roma communities with the bright drama characteristic of his creative style, the psychological depth of genre scenes and individual images, the spectacle of the landscape, which is generally characteristic of the artist’s works. The scientific novelty of the research is the author’s introduction of the materials, dedicated to the study of the specifics of the Roma theme in the works of the domestic genre of Mihály Munkácsy, the world-famous realist artist. Practical significance. Praсtical Significance. The practical significance of the study is to enrich the information about the artistic, stylistic and plot depictions of the Roma, their life, customs and traditions in the works of Mihály Munkácsy. The obtained results prove the perspective of the Roma themes study in works of fine art. Research materials can be used for the attribution of works of art.